Potential silt as adsorbent in removing methylene blue from aqueous solution / Nurain Ramle ...[et al.] - Ramle, Nurain
There is little study about silt that was used as adsorbents for the removal of methylene blue from wastewaters. Therefore, the potential of silt as adsorbent to remove or adsorb the methylene blue dye from waste water were studied. As the water pollution problems have been increasing from year to year and dye waste is one of the major contribute to the water pollution, the common chemical and physical treatment such as reverse osmosis and membrane filtration are not economically feasible. Therefore, the parameters such as effect of adsorbent dosage, effect of initial concentration of methylene blue, effect of pH, and effect of contact time was conducted to study the use of adsorbent silt. The adsorption was study and observed by using Equiptronics single beam u.v. visible spectrophotometer. The result shows for the effect on adsorbent dosage, effect on initial concentration, effect on pH, and effect on contact time that the adsorption of methylene blue increasing as the adsorbent dosage is decreasing, the initial concentration increasing, at the optimum pH which is 3 and as the contact time increasing respectively. Therefore, silt shows the positive result towards all experiment that has been conducted and have high potential to be an adsorbent.